PENGGUNAAN KAYU MANIS (Cinnamomum burmani) UNTUK MENGATASI KETENGIKAN PADA MINYAK KELAPA SECARA TRADISIONAL - - Kadir; Shabri Putra Wirman; Sri Fitria Retnawaty; Aji Suroso (LPPM Universitas Muhammadiyah Riau, 2015)
Coconut oil is an oil produced from coconuts. Based on the high levels of saturated fatty acids and lauric acid (anti-microbial) makes coconut oil as an oil that has the highest quality of other oils. But if oil is stored in a long time it will cause rancidity. Rancidity can be caused by several factors such as oxidation and hydrolysis reactions. One way to overcome this is to add antioxidant rancidity. Antioxidants can be found in everyday life, such as the onion, cloves, betel leaf and cinnamon. In this study using cinnamon oil as an antioxidant and pH were tested for physical parameters such as viscosity, Density, conductivity, resistivity, and the smell test. The results of the pH test and demonstrate physical if cinnamon can prevent oil from rancidity based on the length of storage. And the addition of cinnamon to a maximum of 8 grams are in 50 ml of coconut oil has a pH value, Viscosity, Density, conductivity, resistivity, and the test odors better than the other samples.